Divergent responses of plant functional traits and biomass allocation to slope aspects in four perennial herbs of the alpine meadow ecosystem - Zhou, Tianyang; Du, Wentao; Wang, Jinniu; Zhang, Lin; Gao, Jing; Shi, Ning; Wang, Lihua; Wu, Yan; Tian, Binghui (Frontiers in Plant Science, 2023)
Slope aspect can cause environmental heterogeneity over relatively short distances, which in turn affects plant distribution, community structure, and ecosystem function. However, the response and adaptation strategies of plants to slope aspects via regulating their physiological and morphological properties still remain poorly understood, especially in alpine ecosystems. Here, we selected four common species, including Bistorta macrophylla, Bistorta vivipara, Cremanthodium discoideum and Deschampsia littoralis, to test how biomass allocation and functional traits of height, individual leaf area, individual leaf mass and specific leaf area (SLA) respond to variation in slope aspect in the Minshan Mountain, eastern Tibetan Plateau. We found that the slope aspect affected SLA and stem, flower mass fraction with higher values at southwest slope aspect, which is potentially related to light environment. The low-temperature environment caused by the slope aspect facilitates the accumulation of root biomass especially at northeast slope aspect. Cremanthodium discoideum and Deschampsia littoralis invested more in belowground biomass in southeast and southwest slope aspects, although a large number of significant isometric allocations were found in Bistorta macrophylla and Bistorta vivipara. Finally, we found that both biotic and abiotic factors are responsible for the variation of total biomass with contrasting effects across different species. These results suggest that slope aspect as an important topographic variable, strongly influences plant survival, growth, and propagation. Therefore, habitat heterogeneity stemming from topographic factors (slope aspect) can prevent biotic homogenization and thus contribute to the improvement of diverse ecosystem functioning.